Порівняльна ефективність полімерних додатків при зменшенні втрат енергії в трубопроводах - Чернюк, Володимир; Жук, Володимир (Видавництво Національного університету «Львівська політехніка», 2001)
In the paper the technique of definition of technical and economic efficiency of the hydrodynamic active additives which are used for reduction of a turbulent friction in pipelines is developed. The criterion of efficiency of the additives is offered. With use of experimental results received by the authors, the range of economically favourable use of the polyacrylamide and polyoxyethylen additives is determined.